Seismotectonic and Geological Mapping around the High and Middle Atlas Junction: Integration of Satellite Imagery and Seismic Analysis in the Tizi N’Isly Basin, Morocco - Najim Abdelkarim; Timoulali Youssef; El Hilali Mohamed; Bouiflane Mustapha (E3S Web of Conferences)
The Tizi N’Isly basin, located between the Central High Atlas and Middle Atlas of Morocco, features a complex geological and seismic profile. This study aims to precisely identify areas of vulnerability, seismic zones, and regions exhibiting seismic amplification. The High Atlas is known for its seismic activity, with a notable earthquake of magnitude 6.8 occurring on September 8, 2023, at a depth of 10 km, attributed to an unidentified fault. This event, followed by significant aftershocks, represents the most substantial seismic activity in Morocco since the 1960 Agadir earthquake (magnitude 5.9). Our research combines geological mapping, lineament extraction from satellite imagery, and seismic analysis is to understand the surface and subsurface geology and tectonics. Processed satellite images enhance geological features, facilitating the identification of faults and fractures. Geostatistical analysis of meso-Cenozoic terrain fracturing reveals that lineaments predominantly align with NNE-SSW to NE-SW directions, with additional minor fracture directions. The seismic activity observed is closely linked to faults within this zone, highlighting regional weaknesses.